Performance evaluation and modelling of a small-scale biomass gasifier - Nsamba, Hussein Kisiki (2018)
Many parts of the World have remained underdeveloped due to the lack of access to electricity. Developing and promoting alternative energy sources from renewable materials would assist to mitigate the energy crisis in many parts especially in the World. This research examined the possibility of using a 10KW power pallet as a sustainable energy generation system especially for energy poor areas. This was achieved through the gasification of woodchips at varying moisture content, varying gasification times and at varying electrical loads while investigating the numerous changes in the major factors affecting gasification such as temperature, fuel consumption rate, equivalence ratio (ER), quality of the producer gas, heating value, carbon conversion efficiency as well as the cold gasification efficiency of the gasifier. Experimental data was analysed and interpreted by one way Analysis of Variance (Anova) to establish a relationship on the effect of the major factors affecting gasification as investigated in this study. It was discovered that the gasifier is an autothermal system that maintains a steady state of thermodynamic equilibrium for longer hours as long as the gasifier is constantly supplied with a drier fuel. The gasifier stably and optimally operates with woodchips of moisture content less than 10% to produce an energy rich gas for gasification times longer than six hours to yield a gas rich in Hydrogen (H2), Carbon monoxide (CO) and methane (CH4) at a respective concentration of up to 18.1%, 25.3% and 2.2% with a corresponding Higher Heating Value (HHV), Cold Gas Efficiency (CGE) and gas production rate of 6.4MJ/m3, 75.8% and 2.34m3/kg respectively. The reactor takes longer time to attain thermodynamic equilibrium once operated with woodchips of moisture content above 15%. This subsequently affects the quality of producer gas yielding a gas of low calorific value that would even clog the engine. The moisture content of the wood chips was found to play a very significant role in determining the values of temperatures attained and subsequently determining the quality of producer gas. The gasifier was found to produce the required energy up to the design capacity of 10KW required for several industrial applications. Increasing the engine throttle valve increased the frequency of the engine and subsequently the voltage. The designed energy output of up to 10KW could only be produced if the engine frequency was 60HZ and could be lower if the engine operated at a lower frequency. A thermodynamic equilibrium model was further developed to predict the composition of producer gas going to the engine. The thermodynamic equilibrium model yielded a gas composition of 25.99%, 23.92%, and 0.42% for CO, H2 and CH4 respectively that was in good agreement with the experimental results at 850 ºC and ER of 0.27. Similarly, the modelled gasification temperature of 870.85ºC corresponds with a minor deviation of 2.5% with the experimental gasification temperature of 850ºC. The exhaust stream composition contained Carbondioxide (CO2) of upto 20% which is on the higher side because air was used as the gasifying agent and the gasifier was completely autothermal. Such CO2 concentration ought to be lowered if the gasifier is to be adopted as a sustainable renewable energy system. The gasifier was found to operate better with wood chips in the size range between 1.3cm – 4.0cm as very fine wood chips would block the flow of air hence compromising on the sustainability of the exothermic reactions and bigger wood chip particles would not be easily broken down by the auger hence resisting the flow of the woodchips into the reactor. Operating the gasifier at optimal conditions yields a gas of high calorific value good enough to make it a reliable standalone system that could be integrated into sustainable bioenergy systems.